The question of succession during the reign of Sultan Abdul Hamid II, 1876-1909 - boudjellal, kadour; nemir, Hocine (The Algerian Historical Journal, 2026)
This study deals with a fundamental problem in the history of the Ottoman Empire, namely the caliphate system, which is considered as a system of government followed by the Ottoman Empire in its rule of the Islamic world, and it had decisive effects and direct repercussions on the political, cultural and social transformations that the region witnessed during that period. Historians have disputed the issue of the caliphate after its transition to Ottoman rule. For this reason, this study came to highlight the issue of succession under Ottoman rule, with a focus on the reign of Sultan Abdul Hamid II, and to highlight his efforts in reviving the idea of succession through his methods and projects. We also review domestic and international reactions to the idea of a revival of the caliphate.